Gamification of Tug of War Based on Interactive Flat Panel (IFP) on Motivation and Mathematics Learning Outcomes of Third Grade Elementary School Student - Jarno, Moh. Syalman alfaritzi; Yanuardianto, Elga; Crismono, Prima Cristi (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the Interactive Flat Panel (IFP)-based tug-of-war gamification on the motivation and mathematics learning outcomes of elementary school students. The study used a quantitative approach with a one group pretest–post-test design involving 28 third-grade elementary school students in Jember Regency. The research instruments were learning outcome tests and motivation questionnaires based on the ARCS (Attention, Relevance, Confidence, and Satisfaction) model. Data were analyzed using normality tests, N-gain tests, and paired samples t-tests. The results showed that there was a significant increase in student learning outcomes and motivation after the implementation of IFP-based gamification. The average learning outcome score increased from 56 to 87 with an N-gain of 0.71 (high category), while learning motivation increased from 57 to 80 with an N-gain of 0.52 (moderate category). The results of the paired samples t-test showed a significant difference between the pretest and post-test in both variables (p < 0.05). These findings indicate that the integration of gamification and IFP media not only increases student learning engagement but also strengthens conceptual understanding through interactive and collaborative learning experiences. This research provides a novel contribution to the development of classical gamification-based mathematics learning, particularly through an IFP-based tug-of-war game model that can accommodate direct group interaction.